Sensing Platform for Two-Phase Flow Studies - Eduardo N. Dos Santos; Aluisio Do Nascimento Wrasse; Tiago P. Vendruscolo; Natan S. Reginaldo; Gabriel Torelli; Rafael F. Alves; Bruna P. Naidek; Rigoberto E. M. Morales; Marco J. Da Silva (IEEE Access, 2019)
This paper describes the development and application of a sensing platform which consists of fast conductance sensors and proper data acquisition and management software which aims at the investigation of two-phase flow parameters in pipelines. A number of sensing nodes are connected through a network which allows monitoring the flow at different pipeline positions. In addition, a data management Web-based platform is presented in order to store and manage the massive volume of data generated by data acquisition. The sensor electronics has been evaluated in temporal response and the capability to measure the parameters such as void fraction time series and structure velocities. The preliminary study of horizontal two-phase flow experiment is presented showing the capability of the developed platform to monitor flow parameters along a pipe.